Implementasi Manajemen Mutu sebagai Upaya Meningkatkan Mutu Lulusan di MTs Al Huda Sumberjo Tunglur Badas - Umi Salamatud Diniyah; Mustajib (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
Quality is something that satisfies the needs of customers. quality education is an education that all components have the requirements and conditions that customers want and cause satisfaction, this research aims to describe the planning of quality improvement of graduates in MTs Al-Huda, implementation of quality improvement in MTs Al-Huda, and evaluation of quality improvement of graduates in MTs Al-Huda, Planning in the institution in ways such as strengthening the curriculum, Improving the quality of Educator Resources, and teachers are more creative in delivering materials to children so that the material is delivered properly , Implementation in the institution is teachers provide materials to their students as creatively as possible, teachers often review materials at the end of learning, and teachers provide tutoring to students, especially un subjects, this research uses qualitative approach, data collected using interview techniques, observation and documentation.